EFFECT OF COATING THICKNESS ON CORROSION BEHAVIOR OF ELECTROLESS QUATERNARY NICKEL ALLOY DEPOSIT IN 3.5 wt% NaCl SOLUTIONS - Zaimi, M.; Noda, K. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Metal additive can be added into electroless Ni-Palloy matrix to improve various characteristic, particularly corrosion resistance. Previous studies show that the decreases plating bath pH, increases the phosphorous content in the nickel alloy coatings, improving the corrosion resistance in 3.5 wt% NaCl solutions. However, the true effect of various plating bath pH on corrosion resistance of the nickel alloy is need to be study due to its effect on deposition rate. In this study, electroless quaternary nickel alloy is deposited on pure iron coupon with copper and zinc as metal additive in the plating bath solution. The deposition is done at various plating bath pH and producing approximately the same thickness to verify the plating bath pH effect. The coated coupon is then immersed into 3.5 wt% NaCl solution for anodic polarization curve measurements. From the results, the nickel alloy deposited at similar thickness exhibit almost identical corrosion potential, hence, similar corrosion resistance regardless the effect plating pH on the nickel alloy composition.